Do Agricultural Teachers Differ in Professional Knowledge? - Nazri, Ibrahim (Universiti Putra Malaysia Press, 1993)
The study compares the professional competency of two groups of agricultural teachers. The first group comprised teachers with preservice teacher preparation and the other consisted of teachers without such preparation. The study utilised an ex post facto type of research design. The dependent variable, professional knowledge competence, was measured by a 50-item, multiple-choice test. Seven extraneous variables were identified and tested. Seventy-one teachers with preservice preparation and seventy teachers without such preparation participated in the study. The findings showed that teachers with preservice teacher preparation scored significantly higher than teachers without such preparation. Based on the analysis of results of the significance tests on the extraneous variables, it was concluded that teacher qualification could offer a plausible explanation for the difference in professional knowledge competence among the two groups of teachers. Therefore, it is recommended that the professional knowledge competence of agricultural teachers be recognised as the basis of teacher preparation.